Technology adoption model on cloud computing e-learning for higher education - Abdulsaeed, Ali A (2022)
The advancements of information technology infrastructure along with the extremely high demands and expectations of learning solutions today have directed the e-learning community towards the centralization of learning resources. Thus, delivering the e-learning content to students who have different backgrounds, interests, and locations allows service providers to host their proprietary learning resources over a unified network. Cloud computing with its powerful and sophisticated capabilities and features is highly a potential solution to act in such a learning scenario. However, the technological, environmental and organizational factors may affect the process of maintaining secured and effective software applications that are necessary to manage learning resources for any learning providers in integrity and secure environment. In addition, those factors are dynamic and in such a way due to the limited number of studies that are concerned with critical factors that impact the adoption of e-learning and learning management solutions in Iraq’s universities. Therefore, the main objective of this research is to propose a mode that examines how technological, environmental and organizational factors influence several aspects of cloud computing elearning utilization and adoption in higher education institutions in Iraq. A quantitative research method was adopted, meanwhile, a questionnaire was gathered from 262 information technology staff and managers who were randomly selected from different academic institutions in Iraq. Two analyzing tools, i.e. Statistical Package for the Social Sciences and Partial Least Squares were utilized to study the impact of the adopted factors. The finding of this research shows that the technological, organisational, environmental, and usability factors play a major role in cloud e-learning adoption in Iraq. The results of the analysis revealed a set of factors which are cost saving, compatibility, complexity, privacy and security, integrity, relative advantage, quality system and service, top management support, technology readiness, competitor pressure, regulation and reputation, trading partner pressure, trust, ease of use and perceived usefulness were recognized to have a significant impact on adoption cloud-based e-learning solutions in higher education institutions in Iraq. These reveal crucial implications and are of much value to researchers and e-learning professionals in Iraq. In addition, the new model developed in this study was validated to be more effective for the adoption of cloud computing based on e-learning in Iraqi higher education organizations.